संवृद्धिकालागि पर्यटन क्षेत्रको दीगो विकास आवश्यक छ {Sustainable Development of the Tourism Sector is necessary for Prosperity} - Sharma, Prem (Journey for Sustainable Development and Peace Journal, 2024)
Not Available.